The experiments to determine the electron capture and β-decay of 8B into the highly excited states of 8Be. (December 2020) - Viñals, S; Borge, M J G; Tengblad, O; Nácher, E; Benito, J; Figuera, P; Fraile, L M; Fynbo, H O U; Gad, A; Jensen, J; Jonson, B; Lica, R; et al.
Abstract: The main goal of this work is to study the structure of the highest energy states in 8 Be populated following the β +-decay and the electron capture (EC) of 8 B. With this aim, two experiments were performed at ISOLDE-CERN in 2017 and 2018. The first experiment had the aim to resolve the 2 + doublet at 16.6 and 16.9 MeV, in order to study their isospin mixing. The second experiment aimed to determine a value or give an experimental upper limit to the branching ratio of the exotic EC-p decay. In this paper, we present the experimental setups and we discuss the analysis and present the preliminary results obtained so far.